Work Culture Implementation in Vocational High School - Santosa, Winda Pratiwi; Sari, Dhany Efita; Ahmad, Noor Lela (Proceedings International Conference on Education Innovation and Social Science, 2022)
The purpose of this study is to detail the process of SMK Negeri 6 Surakarta's work culture implementation as well as the challenges that the school has encountered. The ethnographic research design is used in this study's qualitative investigation. The Head of the Institutional Accounting and Finance Expertise Program, the Institutional Accounting and Finance Laboratory Instructor, the Institutional Accounting and Finance Instructor, and the Accounting and Financial Institution students from SMK Negeri 6 Surakarta served as the study's resource participants. In this study, observation, interviews, and documentation were employed as data collection methods. The researchers employed source triangulation to ensure the accuracy of the data.